Keratinized mucosa augmentation guided by double xenogeneic collagen matrix membranes around implants in the posterior mandible: A case report. Issue 3 (22nd January 2021) - Han, Chunyu; Cai, Qing; Li, Baosheng; Li, Yuyang; Liu, Yanqun; Yu, Haina; He, Mengxiao; Meng, Weiyan
Abstract: Rationale: Traditional free gingival graft (FGG) technique is usually used for patients with insufficient peri-implant keratinized mucosa. However, this technique often requires a second surgical area which increases the pain as well as the risk of infection in patients. Xenogeneic collagen matrix (XCM) membrane technique can obtain good results for keratinized mucosa increment. Patient concerns: The patient was a 66-year-old healthy female with loss of left mandibular first molar and second molar (FDI #36, #37) for 5 years. Two implants were placed submucosally for 3 months with no interference, while a stage II surgery was needed. Diagnosis: Probing depth measurements suggested that the mesial, medial, and distal widths of buccal keratinized mucosa within the edentulous area were 0.5, 0.5, and 1 mm, respectively, which were insufficient to maintain the health of peri-implant tissues. Interventions: Keratinized mucosa augmentation guided by XCM membranes was performed to increase the inadequate buccal keratinized mucosa. Outcomes: After 2 months of healing, the widths of mesial, medial, and distal buccal keratinized mucosa were 4, 3, and 3 mm, respectively, and the thickness of the augmented mucosa was 4 mm. Then a stage II surgery was followed. The patient was satisfied with the outcomes of keratinized mucosa augmentation. Lessons: Keratinized mucosa augmentation guided by double XCM membrane technique can be applied to cases with keratinized mucosa width within 2 mm around implants.